Study on Spatial and Seasonal Variation in APTI of Tree Species along Roads of Shivalik Foothills in Himachal Pradesh - Bhardwaj, Anuja; Aggarwal, R. K.; Bhardwaj, S. K. (International Journal of Bio-resource and Stress Management, 2021)
The present study was conducted during the year 2018-2019 to determine the impact of road on Air Pollution Tolerance Index (APTI) of plants growing along the road. A comparative study was done between three roads viz., National highway, State highway and Link Road. Among three roads, link road can be considered as control because vehicular emissions were minimal or non-existent. Three plants (Dalbergia sisso, Mangifera indica and Ficus palmata) were selected as per their uniform presence along all three roads. Four biochemical parameters viz., ascorbic acid, total chlorophyll, leaf extract pH and relative water content were used to calculate the air pollution tolerance index. Season wise maximum ascorbic acid, leaf extract pH and relative water content was observed during post monsoon season whereas total chlorophyll content was observed during pre monsoon season. The APTI of the selected plant species ranged from 8.23 to 10.76 during pre-monsoon and 9.03 to 11.09 during post-monsoon. Anticipated Performance Index (API) was in order of Mangifera indica with highest API grade (6) and it was excellent among plants followed by Dalbergia sisso (5) in very good and Ficus palmata (3) in moderate. Student t-test analysis of seasonal variation of biochemical parameters in leaf of selected tree species was carried out and it was observed that there was significant seasonal effect on mean values of ascorbic acid content and APTI whereas there was no impact of seasons on total chlorophyll content, leaf extract pH and relative water content.